Freelancing expertise : contract professionals in the new economy - Osnowitz, Debra (Ithaca : ILR Press, 2010)
Contract work is more important than ever-for better or for worse, depending on one's perspective. The security once implied by a full-time job with a stable employer is becoming rarer, thereby erasing one of the major distinctions between "freelance work" and a "steady gig." Why hang on to a regular job for the sake of security if security can no longer be assumed? Instead, contractors, hired temporarily for specific knowledge and skills, market their expertise as they move from project to project. Even though their employment is precarious, a great many consider freelancing preferable to holding a "regular" job: the control they feel over their time and careers is well worth the risks that come with relatively uncertain cash flow. Freelancing Expertise is a qualitative study of decision making, work practices, and occupational processes among writers and editors who work in print and Web communications and programmers and engineers who work in software and systems development. Debra Osnowitz conducted sixty-eight extended interviews with representatives of both groups and twelve interviews with managers and recruiters, observed four different work settings in which contractors work alongside employees, and monitored blogs and online discussions among contractors. As a result, she provides a unique and sensitive assessment of a cultural shift in occupations and organizations.Osnowitz calls for a reconfiguration of the employer/employee relationship that accepts more variation and flexibility: just as "freelancing" has, over time, taken on many traits considered characteristic of traditional career paths, so might regular jobs make themselves more appealing to today's workforce by mimicking some of the positive aspects of transactions between clients and contract workers.
Two occupations with divided labor markets -- Assessing options, making choices -- Performing expertise -- Managing marginality -- Collegial networking, occupational control -- Extra-organizational careers -- Work relations reconsidered.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Self-employed -- United States; Independent contractors -- United States; Consultants -- United States; Professional employees -- United States; Temporary employment -- United States; Travailleurs indépendants -- États-Unis.; Entrepreneurs indépendants -- États-Unis.; Consultants -- États-Unis.; Professionnels salariés -- États-Unis.; Travail temporaire -- États-Unis.; BUSINESS & ECONOMICS -- Outsourcing; Consultants; Independent contractors; Professional employees; Self-employed; Temporary employment; United States